PENGARUH PEMBERIAN BEBERAPA DOSIS KOMPOS KULIT BUAH KAKAO DAN DOLOMIT TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DI MEDIA ULTISOL - Imanuel Jhon Hansen (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
The aim of research to determine the effect of compost main pod husks and dolomite as well as their interaction on the growth of cocoa seedlings in media ultisol. Research conducted at the Experimental Farm, Faculty of Agriculture, University of Riau from November 2015 until February 2016. Research in the form of factorial experiment using completely randomized design (CRD). The first factor pod husks compost comprises four levels (0, 75, 100 and 125 g / polybag) and the second factor dolomite consists of three levels (0, 10, and 20 g / polybag), each combination treatment was repeated 3 times. Parameters measured were plant height, leaf number, stem diameter, and leaf area. Each parameter the observed data were statistically analyzed using analysis of variance and test of Duncan's New Multiple Range Test (DNMRT) at 5% level. The results showed the effect of compost pod husks dose of 125 g / polybag significantly increased plant height, stem diameter, number of leaves and leaf area while dolomite dose of 20 g / polybag no real effect except leaf area compared with no treatment. Interaction pod husks compost dose of 100 g / polybag and dolomite dose of 20 g / polybag increase stem diameter, number of leaves and leaf area significantly compared without compost pod husks and dolomite but less tangible than other combinations.